HUBUNGAN PENGETAHUAN DAN TEKNIK MENYUSUI DENGAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS PENGASIH II KABUPATEN KULONPROGO - Handayani, Lina; Yunengsih, Yunengsih; Solikhah, Solikhah (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2014)
ABSTRACT Breastfeeding is the ideal food for babies. Ignorance mother about the importance of breastfeeding, how to breastfeed properly, and launched an aggressive marketing by manufacturers of infant formula, an inhibiting factor for the formation of awareness of parents in providing exclusive breastfeeding. This study aimed to determine the relationships between knowledge and techniques of breastfeeding with exclusive breastfeeding in the area of Puskesmas  Pengasih II,  Kulonprogo.This research employed cross sectional design. The population was all mothers with babies six to 12 months with total sample 142 mothers. The data analysis employed chi square test with alpha significance=5%.  There were relationships between knowledge (p = 0.006) and feeding techniques (p = 0.002) with exclusive breastfeeding.   Keywords: knowledge, breastfeeding techniques, exclusive breastfeeding. Kesmasindo, Volume 6,( 3) Januari 2014, Hal. 232-239